2015
DOI: 10.1097/qad.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

Trends in and correlates of CD4+ cell count at antiretroviral therapy initiation after changes in national ART guidelines in Rwanda

Abstract: Background Initiation of antiretroviral therapy (ART) in the advanced stages of HIV infection remains a major challenge in sub-Saharan Africa. This study was conducted to better understand barriers and enablers to timely ART initiation in Rwanda where ART coverage is high and national ART eligibility guidelines first expanded in 2007–2008. Methods Using data on 6326 patients (≥15 years) at five Rwandan clinics, we assessed trends and correlates of CD4+ cell count at ART initiation and the proportion initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 26 publications
(42 reference statements)
9
29
1
Order By: Relevance
“…In addition to faster progression from diagnosis to ART initiation, we found some evidence that raising CD4 thresholds led to increased care‐seeking, at least in the short run, a phenomenon that has been reported elsewhere 27. We found the greatest increase in new patients at higher CD4 counts, who would not likely have been eligible before the policy change.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition to faster progression from diagnosis to ART initiation, we found some evidence that raising CD4 thresholds led to increased care‐seeking, at least in the short run, a phenomenon that has been reported elsewhere 27. We found the greatest increase in new patients at higher CD4 counts, who would not likely have been eligible before the policy change.…”
Section: Discussionsupporting
confidence: 75%
“…However, to our knowledge, no study has evaluated the causal impact of large ART eligibility expansions on previously eligible patients. One study in Rwanda found an increase in the median CD4 count at enrolment in care following extension of ART eligibility to patients with CD4 ≤ 350 cells/μl, but did not examine the specific impact on the sickest patients 27. Another study in rural KwaZulu‐Natal, South Africa, found that treatment initiation within 3 months of first clinic visit did not change for the sickest patients after this guideline change 28; however, this analysis did not control for long‐term secular trends.…”
Section: Introductionmentioning
confidence: 99%
“…We used a data collection tool that was previously described, and that was developed using the federal ministry of health HIV care/ART entry and follow-up forms used in the ART clinic of the Hospital (Naftalin et al, 2015;Mutimura et al, 2015;Luz et al, 2014;Kanters et al, 2014;Calmy et al, 2012;Boulassel et al, 2012;Wright et al, 2011;Waters et al, 2011;Okulicz et al, 2010;McKinnon et al, 2010;Lok et al, 2010). Data sources included the pre-ART registration, lab requests, monthly cohort and follow up forms, the ART intake form, the patients' card, and the death certificate.…”
Section: Data Collection Toolmentioning
confidence: 99%
“…The proportion of patients enrolling into pre-ART care in this study, both at the VCT and OPD departments before as well as after the introduction of PITC, was among the lowest reported in SSA Mutimura et al, 2014;Rosen & Fox, 2011). Our survey among patients who were not registered at the ART clinic demonstrated that this proportion was an underestimate of patients actually linked to pre-ART care.…”
Section: Discussionmentioning
confidence: 55%